Hubungan Pengetahuan dan Sikap Lansia dengan Kejadian Hipertensi Di Puskesmas Kecamatan Pondok Gede Kota Bekasi Tahun 2013 - Siti Rukayah; Bayati Dewi Wahyu (STIKes Persada Husada Indonesia, 2014)
Hypertension is a form of disorder in the circulatory system which is quite concerning to the publichealth. Year by year, The number of hypertension diseases is drastically increasing in both Indonesia &worldwide. Some of the factors that cause hypertension are heredity, age, gender, race and habits such asexcessive salt intake, overeating / obesity, stress or mental stress and other influences (smoking and drinkingalcohol). This study aims to identify the relationship between knowledge and attitudes of the elderly againsthypertension occurrence at the Pondok Gede Sub-District Public Health Center City of Bekasi. This study usesanalytic survey with cross sectional approach, with the population of all elderly patients aged over 60 yearswho suffer from hypertension. Number of samples were 83 respondents, with data analysis using the Chi-Square. Investigation on the independent variable focused in knowledge and attitude while the dependent variable in hypertension incident.The research outcome indicated the existence of knowledge and attitude against hypertension occurrence in the elderly at Pondok Gede Sub-District Public Health Center City of Bekasi. There is a need to increase health care especially in the elderly by improving health prevention education and how to deal with hypertension at least on a monthly basis so the elderly have ability to manage hypertension through knowledge and good attitude ,thereby reducing the existing risk factors in the elderly . Keywords : knowledge, attitudes, elderly, hypertension